Research Trends of Project-Based Learning Model in Chemistry Learning Through Bibliometric Analysis - Lestari, Nanda Ayu; Liliasari; Irawan, Nisrina Zahira Putri; Musthapa, Iqbal (Universitas Pendidikan Ganesha, 2024)
Chemistry learning has evolved into various interdisciplinary laboratory practicum activities. The Project-Based Learning (PjBL) Model is one of the innovative strategies that can improve students' high-level skills in mastering chemical concepts and applications broadly and deeply. This research aims to conduct a bibliometric analysis of research developments, relevant topics, and future research opportunities related to the use of project-based learning models in chemistry learning applied in the last decade (2014-2024). The keywords used are project-based learning, chemistry learning, and chemistry education. The results of the search through the Scopus database obtained 365 articles published during 2014-2024, then 319 articles were selected based on predetermined criteria. The results showed that the frequency of research on project-based learning in chemistry began to increase significantly in 2018 and reached a peak in 2021. Chemistry topics that are mainly researched using the project-based learning model are organic chemistry, chemical analysis, green chemistry, and chemistry practicum. The potential research in the future are related to ICT-assisted with project-based learning model such as augmented reality in chemistry learning, the implementation of Project-Based Learning model in inorganic chemistry content, and the link between the PjBL model and curriculum development in the field of chemistry education. This study is expected to help researchers who will conduct and determine the main topics relevant to the domain of project-based learning in the context of chemistry learning.